Intraosseous Plating for the Management of Cortical Defects. (February 2018) - Bergin, Patrick F.; Weber, Timothy G.; Gerow, Daniel E.; Spitler, Clay A.; Graves, Matthew L.; Russell, George V.
Abstract : Summary: The management of fractures with segmental bone loss or abundant comminution on the far cortex is often complicated by deformity or frank hardware failure. Using plate constructs that rely on off-axis loading may not be sufficient to support the limb until healing occurs. There are a number of techniques to mitigate this problem, notably the use of intramedullary nails and bicolumnar plating of the fracture. These techniques are not always possible and do come with the biologic cost of additional surgery. In this article, the authors present a technique along with 2 case examples of using plates in an intraosseous location that was described by Dr Mast in his classic orthopaedic text. By placing these plates in the intramedullary space and then interdigitating fixation from the standard cortical plate, a rigid "I-beam" of fixation can be created to mitigate the eccentric loading placed on extraosseous plates. This technique is especially useful in situations in which intramedullary nails are precluded (comminuted intraarticular and some periprosthetic fractures).